Literature Review of Leadership for Youth: Identifying the Most Effective Styles for Change Agents - A A Ngr Bagus Aristayudha (West Science Business and Management, 2024)
According to the UU Kepemudaan, the youth are those aged 16 to 30 who have a vital role in driving change in social, economic, and political domains. The objective of this study is to determine the leadership styles that have a beneficial impact on young people, examine how these styles influence them, and uncover any common qualities among these styles. Although there has been considerable research on leadership, there is a lack of studies explicitly concentrating on youth. Young people display distinct attributes, including a significant reliance on technology and a drive to have a positive impact. Effective leadership styles should elicit inspiration, motivation, and empowerment in individuals. This study used a literature review methodology to investigate the following research questions: What are the most appropriate leadership styles for young people? What impact do these methods have on young people as agents of change? Do these styles share any similar characteristics? The results suggest that transformational, transactional, and supporting leadership have a major impact on young people by increasing their motivation, engagement, and productivity. Typical antecedents encompass well-defined objectives, unambiguous job expectations, assistance, acknowledgment, personal growth opportunities, and consistent evaluation. The study asserts that comprehending different leadership styles is crucial for optimizing the potential of young individuals and suggests additional empirical investigation and examination of the function of technology in leadership.